Travel, Work, and Well-being: Examining the Commuting Habits of Nurses in England & Wales - Jamieson, Michelle; Atherton, Iain (International Journal of Population Data Science, 2025)
Objectives To assess the distance nurses in England and Wales lived from their place of work at point of the 2021 census. This will assess the degree to which their geographical proximity to work may have implications for their own wellbeing and that of their patients. Methods Analyzing census microdata, the dataset used represents a 5% sample of the population of England and Wales. The key outcome of interest was straight-line distance from home to place of work. This will be used to assess the extent to which nurses, who will largely be working shifts, are able to live within reasonable proximity to the hospital, clinic or practice where they are based. Descriptive statistics will be calculated to assess the extent to which socio-demographic characteristics are associated with longer commutes. A matched comparison will be used to assess the extent to which nurses travel compares to the general population. Results Findings will be presented describing distance resided from workplace for nurses and for the matched comparison group and the extent to which being employed in nursing is associated with disproportionate commuter burdens. This is especially important given that most nurses work shifts with potentially fewer travel options. Tables will be presented that describe the socio-demographic composition of both, and the extent to which characteristics are associated with distances travelled. Maps will highlight the extent of geographical variation. Statistical models will then be presented that explore commutes and drivers associated with home-work proximity. These will ascertain the main drivers of workplace commuting distance for both the nursing workforce and matched counterparts from the general working population. Conclusion Findings will be discussed with focus on policy relevance, specifically implications for cost of living, quality of life, and potential implications for nurses’ own health, their ability to care, and workforce retention. These are key concerns regarding local and national housing policies.